2002
DOI: 10.1086/342064
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of a Model of Prediction of Invasive Bacterial Infection Risk among Children with Cancer, Fever, and Neutropenia

Abstract: A risk prediction model for invasive bacterial infection (IBI) was prospectively evaluated among children presenting with cancer, fever, and neutropenia. The model incorporated assessment of 5 previously identified risk factors: serum level of C-reactive protein (CRP) >/=90 mg/L, hypotension, identification of relapse of leukemia as the cancer type, platelet count of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1
16

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 21 publications
5
83
1
16
Order By: Relevance
“…Study done by Santolaya M et al showed the mean age was 7±4 years. 29 Among the study group 64% cases were male; indicating male preponderance and among them 31[62%] were younger than 5 year; similar to the study done by Jacques N and Judith MC.…”
Section: Discussionsupporting
confidence: 83%
“…Study done by Santolaya M et al showed the mean age was 7±4 years. 29 Among the study group 64% cases were male; indicating male preponderance and among them 31[62%] were younger than 5 year; similar to the study done by Jacques N and Judith MC.…”
Section: Discussionsupporting
confidence: 83%
“…The duration of neutropenic phases caused by chemotherapy represents an important risk factor for acquiring nosocomial infections independently of undergoing a HSCT [25][26][27]. In our study we demonstrated that the main significant risk factors for nosocomial CA-BSI acquired during neutropenia are transplantation and the diagnosis and treatment for an AML.…”
Section: Discussionmentioning
confidence: 51%
“…[11,15,16] A recently published study reported 11.1% composite AE outcome in FN patients with in-hospital mortality of (0.7%), PICU admission (4.7%), and fluid resuscitation > 40 ml/kg in (10.1%). [17] Out data also showed that severe myelosuppression was associated with composite AE outcome as patients with more severe neutropenia and thrombocytopenia have a higher risk for AE [13,21].…”
Section: Discussionmentioning
confidence: 99%